1996
DOI: 10.1002/art.1780390814
|View full text |Cite
|
Sign up to set email alerts
|

Increased prevalence of systemic sclerosis in a native american tribe in oklahoma. Association with an amerindian HLA haplotype

Abstract: Objective. To investigate a high prevalence of systemic sclerosis (SSc; scleroderma) in a well-defined population of 21,255 Choctaw Indians residing in 8 southeastern Oklahoma counties who were "users" of Indian Health Services.Methods. A case-control study of 12 SSc cases and 48 matched non-SSc controls (4 per case) was conducted to investigate potential occupational, residential, and infectious exposures, as well as genetic factors which might predispose to SSc. HLA class I1 alleles were determined by DNA ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
157
2
9

Year Published

1998
1998
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 213 publications
(180 citation statements)
references
References 41 publications
12
157
2
9
Order By: Relevance
“…None of the patients or control subjects were known to be first-degree relatives. This population has the highest prevalence of SSc reported, and the clinical disease pattern is relatively homogeneous (20). In addition, in previous studies, we have reported a genetic association/linkage of the fibrillin 1 gene (FBNI) with SSc in this population (20,21).…”
Section: Methodsmentioning
confidence: 75%
“…None of the patients or control subjects were known to be first-degree relatives. This population has the highest prevalence of SSc reported, and the clinical disease pattern is relatively homogeneous (20). In addition, in previous studies, we have reported a genetic association/linkage of the fibrillin 1 gene (FBNI) with SSc in this population (20,21).…”
Section: Methodsmentioning
confidence: 75%
“…The highest prevalence of SSc has been reported in a Choctaw Native American group in Oklahoma (660 cases per million, based on 14 cases) (39). Genetic influences have been proposed to account for this increase but have not yet been definitively identified (39; for review, see ref.…”
Section: Discussionmentioning
confidence: 99%
“…It has an estimated worldwide prevalence between 50 and 300 per one million population. The incidence and prevalence varies geographically and amongst different ethnicities (1,3,16) . In a study carried out in South Africa at Chris…”
Section: Overview Of Systemic Sclerosismentioning
confidence: 99%
“…The non-HLA associated gene IRF8 has been linked to lcSSc and ACA (21) . Choctaw Native Americans have a unique HLA haplotype which is thought to confer SSc susceptibility (16) . These genetic associations may, with further elucidation, help to explain individual susceptibility to SSc, as well as help to explain the driving force behind associations between disease subtypes, laboratory features, and clinical outcomes, which are currently not clearly defined.…”
Section: Overview Of Systemic Sclerosismentioning
confidence: 99%
See 1 more Smart Citation